The multichord stellar occultation on 2019 October 22 by the trans-Neptunian object (84922) 2003 VS2 - Vara-Lubiano, M.; Benedetti-Rossi, G. [UNESP]; Santos-Sanz, P.; Ortiz, J. L.; Sicardy, B.; Popescu, M.; Morales, N.; Rommel, F. L.; Morgado, B.; Pereira, C. L.; Álvarez-Candal, A.; Fernández-Valenzuela, E.; et al. (EDP Sciences, 2022)
Context. Stellar occultations have become one of the best techniques to gather information about the physical properties of trans-Neptunian objects (TNOs), which are critical objects for understanding the origin and evolution of our Solar System. Aims. The purpose of this work is to determine, with better accuracy, the physical characteristics of the TNO (84922) 2003 VS2 through the analysis of the multichord stellar occultation on 2019 October 22 and photometric data collected afterward. Methods. We predicted, observed, and analyzed the multichord stellar occultation of the Second Gaia Data Release (Gaia DR2) source 3449076721168026624 (mÏ = 14.1 mag) by the plutino object 2003 VS2 on 2019 October 22. We performed aperture photometry on the images collected and derived the times when the star disappeared and reappeared from the observing sites that reported a positive detection. We fit the extremities of such positive chords to an ellipse using a Monte Carlo method. We also carried out photometric observations to derive the rotational light curve amplitude and rotational phase of 2003 VS2 during the stellar occultation. Combining the results and assuming a triaxial shape, we derived the 3D shape of 2003 VS2. Results. Out of the 39 observatories involved in the observational campaign, 12 sites, located in Bulgaria (one), Romania (ten), and Serbia (one), reported a positive detection; this makes it one of the best observed stellar occultations by a TNO so far. Considering the rotational phase of 2003 VS2 during the stellar occultation and the rotational light curve amplitude derived (Am = 0.264 ± 0.017 mag), we obtained a mean area-equivalent diameter of DAeq = 545 ± 13 km and a geometric albedo of 0.134 ± 0.010. By combining the rotational light curve information with the stellar occultation results, we derived the best triaxial shape for 2003 VS2, which has semiaxes a = 339 ± 5 km, b = 235 ± 6 km, and c = 226 ± 8 km. The derived aspect angle of 2003 VS2 is θ = 59 ± 2 or its supplementary θ = 121 ± 2, depending on the north-pole position of the TNO. The spherical-volume equivalent diameter is DVeq = 524 ± 7 km. If we consider large albedo patches on its surface, the semi-major axis of the ellipsoid could be ∼ 10 km smaller. These results are compatible with the previous ones determined from the single-chord 2013 and four-chord 2014 stellar occultations and with the effective diameter and albedo derived from Herschel and Spitzer data. They provide evidence that 2003 VS2s 3D shape is not compatible with a homogeneous triaxial body in hydrostatic equilibrium, but it might be a differentiated body and/or might be sustaining some stress. No secondary features related to rings or material orbiting around 2003 VS2 were detected.
Keywords: Kuiper belt objects: individual: 2003 VS2; Methods: observational; Techniques: photometric